Previously unknown and highly divergent ssDNA viruses populate the oceans - Labonté, Jessica M; Suttle, Curtis A (The ISME Journal, 2013)
Single-stranded DNA (ssDNA) viruses are economically important pathogens of plants and animals, and are widespread in oceans; yet, the diversity and evolutionary relationships among marine ssDNA viruses remain largely unknown. Here we present the results from a metagenomic study of composite samples from temperate (Saanich Inlet, 11 samples; Strait of Georgia, 85 samples) and subtropical (46 samples, Gulf of Mexico) seawater. Most sequences (84%) had no evident similarity to sequenced viruses. In total, 608 putative complete genomes of ssDNA viruses were assembled, almost doubling the number of ssDNA viral genomes in databases. These comprised 129 genetically distinct groups, each represented by at least one complete genome that had no recognizable similarity to each other or to other virus sequences. Given that the seven recognized families of ssDNA viruses have considerable sequence homology within them, this suggests that many of these genetic groups may represent new viral families. Moreover, nearly 70% of the sequences were similar to one of these genomes, indicating that most of the sequences could be assigned to a genetically distinct group. Most sequences fell within 11 well-defined gene groups, each sharing a common gene. Some of these encoded putative replication and coat proteins that had similarity to sequences from viruses infecting eukaryotes, suggesting that these were likely from viruses infecting eukaryotic phytoplankton and zooplankton.